Fishes of the western North Atlantic. Anguillidae, Heterenchelyidae, Moringuidae, Chlopsidae, Myrocongridae, Muraenidae, Synaphobranchidae, Ophichthidae, Colocongridae, Derichthyidae, Muraenesocidae, Nemichthyidae, Congridae, Nettastomatidae, Serrivomeridae; Order Saccopharyngiformes, Cyematidae, Saccopharyngidae, Eurypharyncidae, Monognathidae /: Anguillidae, Heterenchelyidae, Moringuidae, Chlopsidae, Myrocongridae, Muraenidae, Synaphobranchidae, Ophichthidae, Colocongridae, Derichthyidae, Muraenesocidae, Nemichthyidae, Congridae, Nettastomatidae, Serrivomeridae; Order Saccopharyngiformes, Cyematidae, Saccopharyngidae, Eurypharyncidae, Monognathidae. Order Anguilliformes : Part Nine ([1989]) - Böhlke, James E
No abstract available